Performance traits of finishing pigs fed mulberry and trichanthera leaf meals - Araque, Humberto; González, Carlos; Pok, Samkol; Ly, Julio (Revista Científica de la Facultad de Ciencias Veterinarias)
A total of 48 commercial crossbred pigs, weighing an average 50 Ó 3 kg were allotted at random in groups of two into six treatments consisting of diets given ad libitum to the animals. There was a control diet (T1) mainly prepared with cereals and soybean meal, and five diets containing sweet potato root meal as the main energy source (40%) and either soybean meal (T2) or mulberry (Morus alba) and trichanthera (Trichanthera gigantea) leaf meals either alone or mixed in the proportion of 24+0 (T3), 16+8 (T4), 8+16 (T5) and 0+24 (T6) percent of the diet respectively. Water solubility and in vitro digestibility of N were best in mulberry as compared to trichanthera. There were no significant differences amongst treatments in feed intake, although a slight depression effect of tree leaf meal on this trait was noted (T3 to T6). Mean daily gain resulted significantly (P < 0.05) higher in treatments T1 to T3 than in those containing high proportions of trichanthera leaf meal (T4 to T6); likewise, a deterioration was observed (P < 0.05) in the food conversion for the treatments (T4 to T6). According to the results herein reported, it should be suggested that in diets for fattening pigs where sweet potatoes root meal is the main energy source, mulberry leaf meal and palm oil in levels of 24% and 6% respectively, determine similar performance traits to others where conventional protein sources are usually included. More research concerning the feeding value of trichanthera leaf meal, or even combinations of mulberry and trichanthera leaf meals should be encouraged to be conducted. Key words: Pigs, sweet potatoes, performance traits, Morus alba, Trichanthera gigantea.